Serological Investigation of Bluetongue Virus Infection in Sheep in Elazığ and Malatya Provinces of Türkiye - Abayli, Hasan; Babacan, Sümeyye (My University, 2022)
Bluetongue (BT) is a non-contagious animal disease spread by blood-feeding midges (Culicoides\rspp.) reported in domestic and wild ruminants in many parts of the world, including Türkiye. \rBluetongue virus (BTV), the causative agent, belongs to the genus Orbivirus in the family \rReoviridae in virus taxonomy. In this study, we aimed to investigate the seroprevalence of BT in \rhealthy sheep in the provinces of Elazığ and Malatya in the Eastern Anatolian region of Türkiye, \rusing a competitive enzyme-linked immunosorbent assay (cELISA; IDEXX, USA) designed for \rdetection antibody against the virion protein 7 (VP7) of BTV. For this purpose, a total of 186 healthy \rsheep (Elazığ, n:100; Malatya, n:86) from five different locations in each province were included in \rthe study, and serum samples were separated from their blood samples collected from their jugular \rvein were used in cELISA. According to the cELISA results in this study, the BT seropositivity of \rsheep in Elazığ and Malatya was 10% (10/100) and 0% (0/86), respectively, while the overall \rseroprevalence was 5.38% for both provinces. Information on the epidemiology of BTV infections in \rElazığ and Malatya provinces is limited. Although this is a small-scale study, the current data \robtained will contribute to the epidemiology of BTV in Türkiye, but more detailed studies are \rneeded in this region.
Keywords: Biyoloji; Parazitoloji; Viroloji; Veterinerlik